Given "3(1+x^2) \\frac{dy}{dx}=2xy(y^3-1)" .
"\\implies \\frac{dy}{y(y^3-1)} = \\frac{2xdx}{3(1+x^2)}"
Now by integration on both sides, we get
"\\int \\frac{1}{y(y^3-1)} dy = \\int \\frac{2x}{3(1+x^2)} dx"
"\\implies \n\\dfrac{\\ln\\left(\\left|y^3-1\\right|\\right)}{3}-\\ln\\left(\\left|y\\right|\\right)\n= \\dfrac{\\ln\\left(x^2+1\\right)}{3}+ \\frac{1}{3}\\ln(c)"
"\\implies \\frac{y^3-1}{y^3 } = c (x^2+1)"
"\\implies \\frac{1}{y^3 } =1- c (x^2+1)"
"\\implies y =\\frac{1}{(1- c (x^2+1))^{\\frac{1}{3}}}" is the solution.
Comments
Leave a comment